Gender equality in science classrooms: teacher perceptions and teaching-learning practices in government primary schools in Dhaka - Ahmed, Maisha (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Masters of Science in Early Child Development, 2021.